Face Mask Embedded with Nanoemulsion for Reducing Facial Skin Adverse Effects Caused by Prolonged Wearing the Mask during COVID-19 Management - Alsantali, Reem I; El-Enin, Hadel A Abo (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Wearing a facemask is one of the precautionary measures for preventing coronavirus disease spread, which causes many facial skin adverse effects. Vitamin-E (TPGS) and olive oil have an efficient effect on skin moistening. Therefore, in this study, face-masks embedded with NE; prepared using olive oil and TPGS, were developed to reduce the long-wearing face mask adverse effect. Methods: Box-Behnken design was used to develop NE formulations which were physically evaluated to select the most stable formulation. Fibroblast cell lines (3T3) were used to examine NE efficacy on dermal cell proliferation and in vitro cytotoxicity possibilities. Face-masks were also examined for 6 hr wearing dermal compatibility on healthy participants. Results: The formulated NE didn’t significantly affect cell proliferation nor had a toxic effect on dermal cells (p<0.05). More than 60% of the respondents were satisfied with masks containing NE. Conclusion: In particular, a face mask embedded with the preparaed selected NE formula could produce emollient feelings during application without retarding the breathing or causing any irritant sensation.
Keywords: Nanoemulsions; Face-mask; Coronavirus disease virus; Olive oil; Vitamin E